1977
DOI: 10.1172/jci108855
|View full text |Cite
|
Sign up to set email alerts
|

Osteomalacia Due to 1α,25-Dihydroxycholecalciferol Deficiency

Abstract: A B S T R A C T Oncogenic osteomalacia is a syndrome in which unexplained osteomalacia remits after resection of a coexisting mesenchymal tumor. We have investigated the mechanism by which a giant cell tumor of bone caused biopsy-proved osteomalacia in a 42-yrold woman. The biochemical abnormalities were: hypophosphatemia; decreased renal tubular maximum for the reabsorption of phosphate per liter of glomerular filtrate; negative calcium and phosphorus balance; hyperaminoaciduria; and subnormal calcemic respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1978
1978
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…In 1977, Drezner & Feinglos recognized impaired 1a-hydroxylation as a characteristic biochemical abnormality of the syndrome, which was later confirmed by Sweet et al (17,18). In 2001, Shimada et al identified FGF-23 as the causative humoral factor of TIO (19).…”
Section: Discussionmentioning
confidence: 96%
“…In 1977, Drezner & Feinglos recognized impaired 1a-hydroxylation as a characteristic biochemical abnormality of the syndrome, which was later confirmed by Sweet et al (17,18). In 2001, Shimada et al identified FGF-23 as the causative humoral factor of TIO (19).…”
Section: Discussionmentioning
confidence: 96%
“…As illustrated in the representative experiment shown in Fig. 1, PTH stimulation resulted in a significant increase of adenylate cyclase activity at a concentration of 10 ug/ml, and the response was a linear function of the hormone concentration from [10][11][12][13][14][15][16][17][18][19][20] ,ug/ml in the preparations from both the PsH and Abnormal Adenylate Cyclase Activity in Pseudohypoparathyroidismcontrol kidneys. Furthermore, the magnitude of the response was not significantly different at each concentration of PTH employed.…”
Section: Resultsmentioning
confidence: 99%
“…Urine specimens were stored at -20°C before analysis of phosphorus (10), creatinine (11), and cyclic AMP (12). The tubular maximum of phosphate reabsorption normalized to glomerular filtration was calculated by the method of Bijvoet (13) as previously described (14). Serum PTH was measured at the Mayo Medical Laboratories, Rochester, Minn., using a carboxy terminal specific assay employing GP1M antibody (15) (normal <40 Al eq/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Carboxyterminal-specific assays were purchased from the Mayo Medical Laboratory (Rochester, Minn.) and The Upjohn Laboratory (Kalamazoo, Mich.); normals were <40 ul eq/ml (18) and <150-375 pg eq/ml (19), respectively. An aminoterminal-specific assay (normal < 0.125 ng/ml) employing a guinea pig antibody raised against the synthetic (1-34) aminoterminal peptide of human PTH was performed in the Duke University Laboratories (20,21) and Dr. Leonard Deftos (University of Califomia, La Jolla, Calif.) measured PTH (normal < 300 pg/ml) by a predominantly carboxy-terminal immunoassay employing previously published methods (22 (29). For these studies serial 2-h urine collections on selected mornings were preceded by a water load of 20 ml/kg body wt.…”
Section: Methodsmentioning
confidence: 99%